A defense of Austrian welfare economics - Fegley, Tate; Israel, Karl-Friedrich (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2024)
Murray N. Rothbard’s Toward a Reconstruction of Utility and Welfare Economics is the defining contribution outlining the Austrian school’s approach to welfare theory. A recent attack on this approach is by Wysocki and Dominiak (2023), who argue, contra Rothbard, that whether an exchange is welfare-enhancing is not necessarily related to whether that exchange is just, and therefore the Rothbardian framework is wrong. This paper shows that their argument misconceives how Austrians treat the concept of welfare. They also misunderstand the crucial role of the principle of demonstrated preference. Properly conceived, Rothbard’s reconstruction remains intact.